The effects of corruption and the fraction of private ownership on the productivity of telecommunication companies. (May 2021) - Brzić, Barbara; Dabić, Marina; Kukura, Frane; Podobnik, Boris
Abstract: The ways in which privatization improves labour and productivity across different sectors of the economy are well known. However, how the country's corruption effects productivity - where corruption is not just an indicator of the misuse of public office, but also a measure of poor governance - remains unclear. To examine this issue, panel data analysis was applied to a set of 62 European telecommunication companies between 2012 and 2019 in order to examine the relationship of corruption and the fraction of private ownership on their productivity … This research hypothesized that higher levels of perceived corruption would present a negative relationship with company's productivity and that a higher percentage of private ownership would have a positive relationship with company's productivity. The results confirmed that the association between corruption and telecommunication companies was negative, while the fraction of private ownership had positive association with productivity. Highlights: Panel data analysis was applied to a set of 62 European telecommunication companies. Corruption has a negative impact on the international business and economy. Private companies are more productive than state-owned companies.